The Development of Module in Mathematics Teaching Materials at PGSD Study Program of University Musamus - Sri Hanipah; Salman Alparis SORMIN; Syahfitriani Br GINTING; Herio Tekdi NAINGGOLAN; Rival HANIP; Margaretha MOKUK (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
The decline in student interest in learning affects learning outcomes, thus putting pressure on lecturers to produce high-quality teaching. To create quality learning, modules that meet the needs are required; thus, research was conducted to produce interactive modules in the development of valid and practical mathematics teaching materials. This study's objective was to produce a module that is interactive in the development of valid and practical mathematics teaching materials. The ADDIE model was used in this development research, but only up to the development stage. One media expert and one material expert acted as research subjects. The results showed that the developed mathematics teaching material development module can be applied to learning in the Musamus University primary school teacher education study program. This is evident from the validation of the material by the material expert, who obtained a score of 92 placings it in the "very feasible" category in terms of the feasibility of the content and presentation. The media validation of the resulting module is in the excellent category, according to the media validation score of the media expert, which is 95. Therefore, it is recommended to use the module as one of the learning resources for developing mathematics teaching materials.